(untitled) (Cardiovascular Journal, 2010)
Background: Trisomy 21 or Down’s Syndrome is the most frequent chromosomal aberration affecting live birth infants with an incidence of 1 in 660 live births. This syndrome is often associated with congenital cardiac lesions, Incidence of which is 40-60 percent. This study was conducted to see the frequency of Down’s syndrome cases and pattern of heart diseases they have in one of the busy non-invasive pediatric cardiac laboratory of the country. Methods: It was a retrospective study conducted in the non-invasive pediatric cardiac laboratory and pediatric cardiac outpatient clinic of a tertiary hospital over a period of two years (November 2007 to October 2009). The entire patients who had Down’s Syndrome and had Doppler echocardiography were included in the study. Results: Out of total six thousand and fifty echocardiography, Down’s Syndrome case was 205 (3.38%). Out of 205 cases, 185 cases were followed up in pediatric cardiac out patient clinic. Twenty cases had not reported in the out patient clinic. Seventeen of those patients had normal cardiac anatomy in Doppler echocardiography. Male were 43.90% and female were 56.09% amongst study group. Most of the patients are young infant (47.32%). Only 2.44% are in more than 10 years age group. Murmur was audible in 86.49% cases in study group and developmental delay was present in 100% of the cases. Doppler Echocardiography was found as most sensitive and specific investigation for detecting congenital heart disease. A-V canal defect was the commonest association (15.60%). Congenital heart disease was not detected in 8.29% cases. Surgical treatment was advised in 52.19% cases, Device closure was advised in 16.59% cases, medical management was advised in 21.46% cases. Conclusion: Down’s syndrome is a very common chromosomal anomaly in our country. Incidence of this syndrome is increasing as number of working women, late marriage and elderly mother increasing. So, multidisciplinary approach for managing this disease should be adopted immediately. Keywords: Down’s syndrome; Congenital heart disease. DOI: 10.3329/cardio.v2i2.6637 Cardiovasc. j. 2010; 2(2) : 184-187